Dynamically Optimized Sequential Experimentation (DOSE) for Estimating Economic Preference Parameters - Jonathan Chapman; Erik Snowberg; Stephanie W. Wang; Colin Camerer (CESifo GmbH, 2024)
We introduce DOSE⸻Dynamically Optimized Sequential Experimentation⸻to elicit preference parameters. DOSE starts with a model of preferences and a prior over the parameters of that model, then dynamically chooses a customized question sequence for each participant according to an experimenter-selected information criterion. After each question, the prior is updated, and the posterior is used to select the next, informationally-optimal, question. Simulations show that DOSE produces parameter estimates that are approximately twice as accurate as those from established elicitation methods. DOSE estimates of individual-level risk and time preferences are also more accurate, more stable over time, and faster to administer in a large representative, incentivized survey of the U.S. population (N = 2; 000). By reducing measurement error, DOSE identifies a stronger relationship between risk aversion and cognitive ability than other elicitation techniques. DOSE thus provides a flexible procedure that facilitates the collection of incentivized preference measures in the field.
Keywords: C81; C90; D03; D81; D90; 330; preference elicitation; risk preferences; time preferences; dynamic experiments; cognitive ability; preference stability